IMPACT OF ABATTOIR EFFLUENTS ON THE PHYSICOCHEMICAL PARAMETERS OF THE MIDDLE REACHES OF THE NEW CALABAR RIVER, NIGER DELTA - AKANKALI , J. A; DAVIES, I. C.; OLALEYE, O. L. (Nigerian Journal of Fisheries, 2023)
Analysis of the impact of abattoir effluents on the physicochemical parameters of the New Calabar River was carried out from February 2020 to July 2020. All parameters were determined using APHA 2340C standards. From the results, the pH ranged from 6.92 to 7.20, while the temperature was from 18.69 to 29.10º C. Salinity ranged from 3.83 to 6.73ppt while chloride was between 5.19 and 9.72mg/l. The Dissolved Oxygen (DO) was between 3.03mg/l to 5.44mg/l while the biological oxygen demand (BOD) values varied from 0.19mg/l to 4.7mg/l, Nitrate was between 2.4 to 3.9mg/L, Phosphate (PO43-) values varied from 8.72mg/l to 13.93mg/l and total alkalinity was from 41.37mg/l to 46.80mg/l. pH was at the highest value in July and the lowest in May. The temperature, BOD, alkalinity turbidity, DO, nitrate, salinity, and total hardness values varied across stations and seasons. Conductivity values were lowest in station 1 and greatest at station 3. The highest conductivity was observed in February and the lowest was in July. Generally, the results were within acceptable levels for WHO (2006) and FEPA (2011). However, continuous discharge of this untreated abattoir and other wastes into this river could eventually render the water unsuitable for human use.